1980
DOI: 10.1111/j.1471-4159.1980.tb09016.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Measurements of Spontaneous and Mitochondria‐Promoted Oxidation of 5,6‐and 5,7‐Dihydroxytryptamine

Abstract: Spontaneous oxygen consumption by 5,6-and 5,7-DHT (dihydroxytryptamine), reiated indoleethylamines, and 6-hydroxydopamine and oxygen consumption by these compounds in the presence of rat liver mitochondria were measured by the polarographic oxygen electrode technique. 5,6-and 5,7-DHT react with oxygen at very different rates (2.7 nmol O,/min and 33.4 nrnol O,/min, respectively) when incubated in buffer, pH 7.2, at a concentration of 1 mM and with different kinetic characteristics. While the oxidation of 5,7-DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Neither the MH ion of 5,6-DHT nor the ions related to its oligomerization products are detectable. These results show the high reactivity of 5,6-DHT in the presence of peroxidase H 2 O 2 and may be explained as due to the reaction pattern proposed by Klemm et al 25 5,6-DHT easily autooxidizes (see Scheme 2), generating an electrophilic o-quinone and other oxidation products which undergo extensive covalent binding with protein nucleophiles both in vitro 26 and in vivo. 27 The data obtained here may be explained by the formation, catalytically induced by H 2 O 2 , of such oxidation products and their fast reaction with peroxidase.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Neither the MH ion of 5,6-DHT nor the ions related to its oligomerization products are detectable. These results show the high reactivity of 5,6-DHT in the presence of peroxidase H 2 O 2 and may be explained as due to the reaction pattern proposed by Klemm et al 25 5,6-DHT easily autooxidizes (see Scheme 2), generating an electrophilic o-quinone and other oxidation products which undergo extensive covalent binding with protein nucleophiles both in vitro 26 and in vivo. 27 The data obtained here may be explained by the formation, catalytically induced by H 2 O 2 , of such oxidation products and their fast reaction with peroxidase.…”
mentioning
confidence: 71%
“…Formation of simple oligomers up to octamers was observed and, even after 360 minutes, the reaction environment remained reddish-brown in color, with the production of only small amounts of precipitate. This comparison shows that only in the reaction of peroxidase H 2 O 2 are reactive species, like those indicated by Klemm et al, 25 produced. Instead, the reaction of 5,7-DHT peroxidase H 2 O 2 leads to the formation of oligomers.…”
mentioning
confidence: 77%
“…Two intracellular catalytic mechanisms have been proposed to explain the evolvement of the strong neurotoxicity potential of 5,7-DHT in vivo following its accumulation in monoaminergic neurons by transporters: 1) mitochondria-(i.e., cytochrome c-) mediated speeding of the autoxidation process of 5,7-DHT (transfer of electrons from 5,7-DHT to the cytochrome-c segment of the respiratory chain (Klemm et al, 1980), and 2) interaction of the hydroperoxide intermediate(s) of autoxidized 5,7-DHT (and its MAO-metabolites) with GSH-peroxidase and formation of trihydroxyindoles which autoxidize (via semiquinone radical intermediates) to give the 4,7-p-quinone of 5-OH-tryptamine (Sinhababu and Borchardt 1985; Tabatabaei and Dryhurst 1998).…”
Section: Hg Baumgarten and L Lachenmayer 590mentioning
confidence: 99%
“…Indole dimers then undergo autoxidation and intermolecular coupling to eventually yield insoluble melanoid polymeric products (Tabatabaie and Dryhurst, 1998). We have shown that rat brain mitochondria accelerate the autoxidation process of 5,6-DHT (Klemm et al, 1980). Under these conditions, oxidation of 5,6-DHT to the corresponding o-quinone is likely to occur.…”
mentioning
confidence: 95%
See 1 more Smart Citation